Clinical results of a new concept of neurothrombectomy coverage at a remote hospital - “drive the doctor” - Seker, Fatih; Möhlenbruch, Markus Alfred; Nagel, Simon; Ulfert, Christian; Schönenberger, Silvia; Pfaff, Johannes; Ringleb, Peter A.; Bendszus, Martin; Herweh, Christian (International journal of stroke, 2018)
Background: Many tertiary care hospitals cannot provide a continuous thrombectomy service due to the lack of a neurointerventionalist. Aims: In this study, we present procedural and clinical results of a new concept in which neuroradiologists of a university hospital provide neurointerventional stroke service to a remote hospital (“drive the doctor”). Methods: All consecutive patients with acute ischemic stroke due to large vessel occlusion of the anterior circulation treated with mechanical thrombectomy after hours at a remote hospital (distance of about 100 km) between 2012 and 2016 were analyzed retrospectively. These patients were compared to a group of patients referred to the above mentioned university hospital for MT over a comparable distance (“drip and ship”). Results: A total of 60 patients were treated by “drive the doctor” and 66 patients were treated by “drip and ship.” Time from onset to imaging was similar in both groups (77 vs. 70 min, P = 0.6847). However, time from imaging to groin puncture was significantly lower in the “drive the doctor” model (112 vs. 232 min, P < 0.0001). Nonetheless, recanalization rate and clinical outcome were similar in both cohorts. Conclusions: “Drive the doctor” is a feasible concept of neurothrombectomy coverage at remote hospitals. The presented data suggest that “drive the doctor” is not inferior compared to established stroke concepts such as “drip and ship” regarding recanalization rate and outcome. However, larger and prospective studies are necessary to confirm this finding.
Gesehen am 27.09.2019